2023
DOI: 10.3389/fnins.2023.1158204
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of mitochondria-associated endoplasmic reticulum membranes (MAMs) dysfunction in Alzheimer’s disease and the potential countermeasure

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease. There are many studies targeting extracellular deposits of amyloid β-peptide (Aβ) and intracellular neurofibrillary tangles (NFTs), however, there are no effective treatments to halt the progression. Mitochondria-associated endoplasmic reticulum membranes (MAMs) have long been found to be associated with various pathogenesis hypotheses of AD, such as Aβ deposition, mitochondrial dysfunction, and calcium homeostasis. However, there is a lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Organelles, including mitochondria and endoplasmic reticulum, have long been implicated in AD pathogenesis. 30 , 31 Gene ontology meta-analysis of top-ranked aggregate proteins (as predicted by NN analysis of network structure) revealed that ∼20% of them are mitochondrial. This suggests two possibilities: ( i . )…”
Section: Discussionmentioning
confidence: 99%
“…Organelles, including mitochondria and endoplasmic reticulum, have long been implicated in AD pathogenesis. 30 , 31 Gene ontology meta-analysis of top-ranked aggregate proteins (as predicted by NN analysis of network structure) revealed that ∼20% of them are mitochondrial. This suggests two possibilities: ( i . )…”
Section: Discussionmentioning
confidence: 99%
“…Schon's laboratory also reported that two important subunits of the catalytic presenilin subunit of γ-secretase, presenilin-1 (PS1) and presenilin-2 (PS2), are highly enriched in MAMs (Area-Gomez et al, 2009 ). MAMs also exhibit lipid raft characteristics, thus providing a favorable environment in which γ-secretase activity can target APP (Li et al, 2023b ). Important enzymes involved in APP processing, such as β- and γ-secretases, are located within lipid rafts.…”
Section: How Aβ Accumulates In Mitochondriamentioning
confidence: 99%
“…Oxidative stress is considered a critical element of the pathogenic process in AD, 39,40 and several studies have identified direct physical connections between many proteins associated with AD pathogenesis and mitochondria or mitochondrial proteins (Figure 2). 34,41 Small molecules are substances that have the ability to interact with a wide range of biological targets, including proteins, enzymes, receptors, and genes. By modifying the activity or functionality of certain targets, they can have therapeutic effects.…”
Section: Alzheimer's Diseasementioning
confidence: 99%